Work Competency and Work Performance among Employees of Fire and Rescue Department Malaysia (JPBM) - Asaari, Muhammad Hasmi Abu Hassan; Husin, Mohd Suhaimi Hj; Desa, Nasina Mat (Universiti Sains Malaysia, 2017)
Saving lifes and rescue missions has been a noble work for Fire and Rescue Department Malaysia (JPBM) employees. They risk their own lifes to save and rescue others. This paper intends to explore their work competencies, namely skills of receiving orders, skills of duty, skills of communication, skills of conflict resolution, and skills of planning an action toward the work performance. A self administered questionnaires were distributed among JPBM employees. The reponse rate was encouraging as they gave full cooperation in the survey. JPBM employees had shown that planning an actions had an impact on thier work performance. But, this did not indicate that their rest of work competence components were not important to them. Moreover, JPBM’s top management needs to capitalize their employees work competence in enhancing their work performance. Management and psychological traninings and courses were seen as major contributor to boost JPBM’s employees work competence that will lead to their work performance.